Nurses' Opinions About Patient Restraint Methods in a Psychiatric Hospital and Their Ethical Sensitivity - Durmaz, Yadigar Cevik; Ersogutcu, Filiz (Slack Inc, 2023)
Methods of restraint can be used to prevent hospitalized psychiatric patients from injuring themselves or others, but use of restraints causes various ethical problems in psychiatric nursing. This study examined the relationship between nurses' sociodemographic characteristics, types of restraint methods used, nurses' opinions about those methods, and their level of ethical sensitivity toward their use. We found the moral sensitivity of our participants to be moderate, and statistically significant differences were found related to marital status, shift type, and restraint method used. Based on our results, we recommend improving nurses' working conditions, increasing their level of ethical knowledge, and expanding the number of studies on these issues. [Psychiatr Ann. 2023;53(12):559-569.]
Keywords: Moral Sensitivity; Physical Restraint; Seclusion; Experiences; Attitudes